Heart rate variability responses to personalized and non-personalized affective videos. A study on healthy subjects and patients with disorders of consciousness - Goizueta, Sandra; Maza, Anny; Sierra, Ana; Navarro, María Dolores; Noé, Enrique; Ferri, Joan; Llorens, Roberto (Frontiers in Psychology, 2025)
IntroductionThe diagnosis of patients with disorders of consciousness (DOC), including those in a minimally conscious state (MCS) and those with unresponsive wakefulness syndrome (UWS), remains a significant clinical challenge. Neurobehavioral assessment primarily relies on motor responses to commands, which are often difficult to interpret due to impaired comprehension and cognitive-motor dissociation, resulting in a high rate of misdiagnosis. While electrical, hemodynamic, and metabolic brain responses, combined with personalized stimuli, have shown promise in improving diagnosis, the role of cardiac activity—less intrusive and time-efficient—remains underexplored.MethodsThis study investigated heart rate variability (HRV) responses to personalized videos of acquaintances versus non-personalized videos of strangers. The study included 17 healthy subjects and 11 patients with DOC. Cardiac responses were recorded and analyzed to compare responses to different stimuli and to examine differences between the two groups.ResultsHealthy subjects exhibited significant differences in several HRV measures in response to both personalized and non-personalized stimuli, whereas patients with DOC did not demonstrate similar differences. Additionally, significant differences were observed in HRV measures between healthy subjects and patients with DOC.ConclusionThese findings suggest impaired emotional processing in patients with DOC. Further exploration of these differences may enhance diagnostic approaches for this patient population, particularly through the integration of HRV-based measures.